Analysis of Exchange Rate and Stock Price Fluctuations in Indonesia - Eldo Anggi Ferdien Saragih; Dewi Mahrani Rangkuty; Rusiadi (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the relationship between exchange rate fluctuations and stock prices in Indonesia. Using daily data from 2010 to 2023, the analysis was carried out through the multiple linear regression method to identify the impact of exchange rate changes on stock prices in the Indonesian capital market. The results show that there is a significant relationship between exchange rate fluctuations and stock prices, where a decrease in the exchange rate tends to have a negative impact on stock prices, especially in import-dependent sectors. In addition, this study also found that there was a difference in stock price response to exchange rate fluctuations between companies listed on the stock exchange and large and small market capitalizations. These findings provide important insights for investors and policymakers in making decisions related to investment and risk management in the stock market. This research is expected to contribute to the literature on financial market dynamics in developing countries, especially Indonesia.